Associations between sleep disorders and anxiety in patients with tinnitus: A cross-sectional study - Wang, Shenglei; Cha, Xudong; Li, Fengzhen; Li, Tengfei; Wang, Tianyu; Wang, Wenwen; Zhao, Zhengqing; Ye, Xiaofei; Liang, Caiquan; Deng, Yue; Liu, Huanhai (Frontiers in Psychology, 2022)
Objective: To investigate the characteristics of sleep disorders and anxiety in patients with tinnitus, their influencing factors, and the role of sleep disorders as mediators. Methods: The general conditions and disease characteristics of 393 patients with tinnitus presented to the Changzheng Hospital of the Naval Medical University from 2018 to 2021 were collected. All patients accepted questionnaires such as Tinnitus Handicap Inventory (THI), Pittsburgh Sleep Quality Index (PSQI) and Self-rating Anxiety Scale (SAS), and then the characteristics and the influencing factors of sleep disorders and anxiety were analyzed. Results: Among the 393 tinnitus patients, 213 cases (54.19%) were diagnosed with sleep disorders, and 78 cases (19.85%) were diagnosed with anxiety, including 25 men (32.1%) and 53 women (67.9%). Binary regression showed that gender, hearing loss, tinnitus severity, and sleep disorders severity were positively associated with anxiety. Multiple logistic regression analysis showed that female gender (OR = 2.526, P = 0.008), hearing loss (OR = 2.901, P = 0.003, tinnitus severity (OR = 1.863, P = 0.003) and sleep disorders (OR = 2.510, P = 0.001) were the independent risk factors of anxiety. The mediating effect of sleep disorders between tinnitus severity and anxiety accounted for 27.88% of the total effect size. Conclusions: Females patients with hearing loss, moderate to severe tinnitus, and sleep disorders were at greater risk for anxiety, with sleep disorders partially mediating the anxiety associated with tinnitus.